Curious astringent joy : an exploration of major Nietzschean echoes in the writing of William Butler Yeats - Bohlmann, Otto (Department of English Language and Literature, 2023)
William Butler Yeats first came under the thrall of / Friedrich Wilhelm Nietzsche in the Dublin summer of 1902. 0 His friend and patron, the New York lawyer John Quinn, had sent Yeats a modest volume of Nietzsche with the imposing title of Nietzsche as Critic, PhiZosopher, Poet and 'Prophet, containing 'Choice Selections from His Works' compiled by Thomas Common, who was to become a major contributor to the Oscar. Levy English edition of Nietzsche's Werke.